Impact Of Capital Structure, Intangible Assets, And Effective Tax Rate On Corporate Performance - Amirah, Nishrina Nurul; Rezalia, Vinny; Lestari, Henny Setyo; Margaretha, Farah (BIMA Journal (Business, Management, & Accounting Journal), 2025)
Purpose: This research investigates the effects of financial management strategies, specifically debt levels, intangible assets, and tangibility, on firm performance, measured by Return on Assets (ROA) and Tobin’s Q. It aims to delineate how these strategies influence operational efficiency and market valuation across various sectors. Methodology: Utilizing a quantitative approach, the study analyzes data from firms in infrastructure, media, and pharmaceutical sectors listed on the Indonesia Stock Exchange over 2019-2023. A fixed effects model is applied to understand the impact of financial strategies on firm performance. Results: The study finds that higher debt levels negatively affect profitability but positively influence market valuation. Intangible assets enhance operational profitability but have a mixed impact on market valuation, indicating a market challenge in valuing these assets accurately. Conversely, tangibility increases profitability but is perceived negatively in market valuation. Findings: The differential impact of financial strategies suggests that firms need to balance their asset and debt management to optimize both profitability and market perception. Novelty and Originality: This research contributes new insights into the nuanced roles of asset management in financial strategy, emphasizing sector-specific financial management practices. It highlights the complex interplay between financial decisions and firm performance, providing a nuanced understanding that aids strategic financial planning. Conclusion: Effective financial management involves balancing debt, tangibility, and intangible assets to enhance firm performance across various metrics. Future research could explore these relationships under different economic conditions and extend findings across other sectors. Type of Paper: Research Article